2003
DOI: 10.1261/rna.2191903
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic regulation of α-actinin alternative splicing by CELF proteins and polypyrimidine tract binding protein

Abstract: The ␣-actinin gene has a pair of alternatively spliced exons. The smooth muscle (SM) exon is repressed in most cell types by polypyrimidine tract binding protein (PTB). CELF (CUG-BP and ETR3-like factors) family proteins, splicing regulators whose activities are altered in myotonic dystrophy, were found to coordinately regulate selection of the two ␣-actinin exons. CUG-BP and ETR3 activated the SM exon, and along with CELF4 they were also able to repress splicing of the NM (nonmuscle) exon both in vivo and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 52 publications
3
118
0
2
Order By: Relevance
“…Finally, it was also shown that PTB binding sites can overlap with enhancer elements. In this case, PTB can compete the binding of activator factors, preventing the formation of an activator complex (46,47). In accord with this model, we identified a complex intronic enhancer element that overlaps with the repressor region.…”
Section: Discussionsupporting
confidence: 55%
“…Finally, it was also shown that PTB binding sites can overlap with enhancer elements. In this case, PTB can compete the binding of activator factors, preventing the formation of an activator complex (46,47). In accord with this model, we identified a complex intronic enhancer element that overlaps with the repressor region.…”
Section: Discussionsupporting
confidence: 55%
“…Therefore, it will be meaningful to examine its functional role, as well as its structure, in more detail and look for differences between the splice variants. Beside U2AF, the repressive role of PTB has been antagonized by many different RNA binding proteins, namely the CELF [13,25] proteins ETR3 and CUG-BP, RBM4 [33], TIA-1 [27,34], Nova [40] and Fox-1 [102]. It will be valuable to gain a better understanding of the molecular mechanisms behind these antagonisms.…”
Section: Discussionmentioning
confidence: 99%
“…Polypyrimidine tract binding protein (PTB) is a ubiquitous regulator of alternative splicing that influences different types of alternative-splicing events (a) PTB represses the N1 "cassette-exon" in the c-src pre-mRNA [7,9,10,103]. (b) PTB represses the "mutually exclusive" SM exon of the a-actinin mRNA [12,13]. (c) PTB regulates the choice of the 3'-terminal exon of the calcitonin/CGRP mRNA [104].…”
Section: The Many Functions Of Polypyrimidine Tract Binding Proteinmentioning
confidence: 99%
“…In the nucleus, CELF proteins regulate pre-mRNA alternative splicing of a subset of transcripts by binding to intronic U/G-rich sequences and communicating with the basal splicing machinery through some as-yet-unknown mechanism (Ladd et al, 2001(Ladd et al, , 2005Charlet-B. et al, 2002a;Suzuki et al, 2002;Zhang et al, 2002;Gromak et al, 2003). In the cytoplasm, CELF proteins can regulate both transcript stability and translation by interacting with A/U-rich sequences in the 3Ј untranslated regions of target mRNAs (Timchenko et al, 2001;Mukhopadhyay et al, 2003).…”
Section: Introductionmentioning
confidence: 99%